Pengaruh Self Assessment System dan Pemeriksaan Pajak terhadap Penerimaan Pajak Penghasilan (PPh) (Studi pada Kantor Pelayanan Pajak Madya Malang Periode 2012-2014) - Harris, . (Jurnal Mahasiswa Perpajakan, 2016)
This study aims to determine the effect of Self Assessment System which is represented by the amount of Tax Payment Slip of Income Tax submitted and Periodic Tax Return of Income Tax reported, Tax Audit as represented by the amount of Underpayment Tax Assessment Letter and Added Underpayment Tax Assessment Letter against the Income Tax Revenue  either simultaneously or partially. The explanatory research is a type of research that is selected in this study . The research data is secondary data, which is the amount of monthly Payment Slip of Income Tax submitted and Periodic Tax Return of Income Tax reported, Tax Audit as represented by the amount of Underpayment Tax Assessment Letter and Added Underpayment Tax Assessment Letter, and Income Tax Revenue for 36 months. Statistical analysis Descriptive and inferential statistical analysis is a method of data analysis used in this study . Here are the results obtained from this study : ( 1 ) the amount of Tax Payment Slip of Income Tax submitted, Periodic Tax Return of Income Tax reported , Underpayment Tax Assessment Letter and Added Underpayment Tax Assessment Letter has significant effect on income tax revenues simultaneously . ( 2 ) the amount of Tax Payment Slip of Income Tax submitted, Periodic Tax Return of Income Tax reported has significant effect on the amount of income tax revenue partially , while the amount of Underpayment Tax Assessment Letter and Added Underpayment Tax Assessment Letter doesn’t have significant effect on income tax receipts partially.Key word: Self Assement Sytem, Tax Payment Slip of Income Tax, Periodic Tax Return of Income Tax, Tax Audit, Underpayment Tax Assessment Letter, Added Underpayment Tax Assessment Letter, Income Tax Revenue ABSTRAK Penelitian ini dimaksudkan untuk mengetahui seberapa besar Self Assessment System yang diwujudkan dalam jumlah SSP dan jumlah SPT serta pemeriksaan pajak yang diwujudkan dalam jumlah SKPKB dan SKPKBT dapat mempengaruhi penerimaan PPh baik secara simultan maupun parsial. Penelitian penjelasan merupakan jenis penelitian yang dipilih dalam penelitian ini. Data penelitian merupakan data sekunder berupa data tiap bulan dari jumlah SSP, SPT, SKPKB dan SKPKBT serta penerimaan PPh selama 36 bulan. Analisis statistik deskriptif serta analisis statistik inferensial adalah metode analisis data yang dipakai dalam penelitian ini. Berikut ini adalah hasil yang didapatkan dari penelitian ini: (1) Jumlah SSP, jumlah SPT, jumlah SKPKB dan SKPKBT berpengaruh signifikan terhadap penerimaan PPh secara simultan. (2) Jumlah SSP, jumlah SPT berpengaruh signifikan terhadap penerimaan PPh secara parsial, sementara jumlah SKPKB dan SKPKBT tidak berpengaruh signifikan terhadap penerimaan PPh secara parsial. Kata kunci: Self Assessment System, SSP PPh, SPT PPh, Pemeriksaan Pajak,           SKPKB, SKPKBT, Penerimaan PPh